Association of the use of diabetes technology with HbA1c and BMI‐SDS in an international cohort of children and adolescents with type 1 diabetes: The SWEET project experience. Issue 8 (9th November 2021) - Marigliano, Marco; Eckert, Alexander J.; Guness, Pravesh K.; Herbst, Antje; Smart, Carmel E.; Witsch, Michael; Maffeis, Claudio; ,
Abstract: Objective: To examine the association between the use of diabetes technology (insulin pump [CSII], glucose sensor [CGM] or both) and metabolic control (HbA1c) as well as body adiposity (BMI‐SDS) over‐time in a cohort of children and adolescents with type 1 diabetes (T1D), that have never used these technologies before. Subjects and methods: Four thousand six hundred forty three T1D patients (2–18 years, T1D ≥1 year, without celiac disease, no CSII and/or CGM before 2016) participating in the SWEET prospective multicenter diabetes registry, were enrolled. Data were collected at two points (2016; 2019). Metabolic control was assessed by glycated hemoglobin (HbA1c) and body adiposity by BMI‐SDS (WHO). Patients were categorized by treatment modality (multiple daily injections [MDI] or CSII) and the use or not of CGM. Linear regression models, adjusted for age, gender, duration of diabetes and region, were applied to assess differences in HbA1c and BMI‐SDS among patient groups. Results: The proportion of patients using MDI with CGM and CSII with CGM significantly increased from 2016 to 2019 (7.2%–25.7%, 7.8%–27.8% respectively; p < 0.001). Linear regression models showed a significantly lower HbA1c in groups that switched from MDI to CSII with or without CGM ( p < 0.001), but a higher BMI‐SDS (from MDI without CGM to CSII with CGM p < 0.05; from MDI without CGM to CSII without CGM p < 0.01). Conclusions: Switching from MDI to CSII is significantly associated with improvement in glycemic control but increased BMI‐SDS over‐time. Diabetes technology may improve glucose control in youths with T1D although further strategies to prevent excess fat accumulation are needed.